Konstruksi Berpikir Kritis dan Pembelajaran Mendalam dalam Buku Teks Bahasa Indonesia: Kajian Linguistik Sistemik Fungsional - Andi Sahtiani Jahrir; Muhammad Tahir (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Makassar, 2026)
The development of critical thinking and deep learning has become one of the primary demands of twenty-first-century education and an essential component of the implementation of the Merdeka Curriculum in Indonesia. In this context, textbooks play a strategic role as pedagogical instruments that shape students’ ways of thinking and learning experiences. This study aims to examine how the textbook Bahasa Indonesia: Anak-Anak yang Mengubah Dunia for Grade VI represents critical thinking skills and deep learning dimensions through the perspective of Systemic Functional Linguistics (SFL). Employing a qualitative descriptive approach, the study used document analysis to investigate learning activities, instructions, questions, and tasks presented in the textbook. Data were analyzed through SFL transitivity analysis and the mapping of critical thinking indicators and deep learning competencies. The findings reveal that the textbook consistently provides learning activities that promote interpretation, analysis, evaluation, inference, explanation, and self-reflection. From an SFL perspective, the instructional discourse is dominated by mental and verbal processes that position students as active meaning-makers through reflection, discussion, argumentation, and problem-solving activities. Furthermore, the textbook integrates the six core competencies of deep learning critical thinking, communication, collaboration, creativity, character, and citizenship across a variety of contextual themes. These findings indicate that the textbook functions not only as a language learning resource but also as a pedagogical tool for fostering twenty-first-century competencies aligned with the goals of the Merdeka Curriculum.